Cultural continuity and change in Kudus Kulon: The urban heritage trialogue - Wulandari, Astari; Atik Suprapti; Agung Budi Sardjono (Institute for Advanced Science Social, and Sustainable Future, 2024)
Physical changes to built heritage are usually a major cause for concern when reviewing approaches to conservation and adaptation to the historic built environment. The hictorical area Kudus Kulon has witnessed significant changes in its environmental conditions, not only includes physical transformation, but also involves the social and economic dynamics that develop around it. Physical changes to built heritage are usually a major cause for concern when reviewing approaches to conservation and adaptation to the historic built environment. This study aims to reveal the changes and continuity of the Kudus Kulon historical area in the context of heritage preservation. This qualitative research employs a case study approach, focusing on Kudus Kulon as a single case. Through observations and interviews with key informants, the aim is to present an unbiased perspective on the intangible aspects. The findings in this study will enrich cultural theory through its ability to dialogue value systems, activities, and artefacts in the context of change and continuity in the historic district of Kudus Kulon. The result shows the continuity of fundamental aspects in the value system (belief, norm, and local wisdom) underscores the resilience of the system and its ability to navigate the complexities of time without compromising the integral values that define its cultural identity. This research provides a strong foundation for future studies to explore the intricate dynamics between core values, societal development, and adaptations on heritage site in urban area, with a specific focus on tangible aspects like artefacts and activities.